BUILDING THE WELFARE OF THE PEOPLE WITH PRODUCTIVE ZAKAT: CASE STUDY AND IMPLEMENTATION - arisman, ari (Medpro, 2022)
The innovative pattern of productive distribution of zakat funds at the empirical level, the process of Islamization of the income distribution system is still relatively new and is still being implemented in small volumes by a number of zakat amil institutions, but it is already showing a direction of optimism. The research aims to find out whether there is a program for utilizing zakat funds launched by the zakat amil institution Rumah Zakat Indonesia. Researchers assume that zakat funds have a productive content that is different from other forms of loans, which of course will shape productivity patterns. The research used qualitative methods, data was obtained from the results of researchers' observations and surveys on the program for utilizing zakat funds for productive programs. The research results show that the utilization program launched by Rumah Zakat Indonesia through an income distribution system, although at an empirical level, is still relatively new, it is already moving towards optimism. The policy of the utilization program through the target dimension is very appropriate, by making the poor as the target recipients of productive zakat funds.